THE ROLE OF JUDGES IN ADJUDICATING DEFAULT CASES CONTAINING ELEMENTS OF ABUSE OF CIRCUMSTANCES IN THE BANKING SECTOR - Wandita Pramesthi; Reka Dewantara; Yenny Eta Widyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
In the Indonesian civil law system, the role of judges is crucial in adjudicating cases involving contractual legal relationships, particularly in banking default cases. Injustice often arises from the abuse of circumstances, where debtors who are in a weak position are often victims of adverse bank policies. Additionally, high interest rates and oppressive contractual clauses pose significant challenges for judges. This research shows that disparities exist in court decisions on abuse of circumstances, creating legal uncertainty. Using a normative juridical approach, this research examines the need for clear legal guidelines from the Supreme Court to establish uniformity in the handling of default cases. Stronger regulations are expected to ensure that judges make more judicious decisions and uphold justice for all parties. This research emphasises the importance of applying the principle of fairness in contracts, so that freedom of contract does not neglect the rights of weaker parties.